Successful treatment with HLA-matched peripheral hematopoietic stem cell transplantation for very severe hepatitis-associated aplastic anemia complicated with multidrug-resistant bacterial and fungal infections: A case report - Li, Hua; Li, Xiaofan; Chen, Xianling; Li, Nainong (Frontiers in Pediatrics, 2022)
Hepatitis associated aplastic anemia (HAAA) is a life-threatening hematologic disorder with characterization of bone marrow failure. Allogeneic hematopoietic stem cell transplantation (HSCT) is the first-line treatment for HAAA. Serious infection and complications in patients with very severe aplastic anemia（VSAA） are the challenges for the efficacy of HSCT. We report a rare case of successful transplantation with HLA-matched peripheral hematopoietic stem cells for a 15-year-old girl who was suffering HAAA with multidrug-resistant (MDR) bacterial and fungal infections. Through effectively controlling infection, grasping the timing of transplantation and adjusting conditioning reginem， the transplantation was successfully performed. Updated data of following-up 26 months after transplantation showed that the patient was still in complete remission with a good quality of life. This case provided a reference to treat severe infected patients with HAAA before HSCT.